Effect of Computer-Based Visualization Model on Students’ Academic Achievement in the Periodic Table Concept in Chemistry - Sunday, Edima; Umanah, Felicia; Ntegwung, George; Akpan, Enobong (Universitas Islam Indonesia, 2026)
This study investigated the effect of a computer-based visualization model on students’ academic performance in the concept of the periodic table in Chemistry in secondary schools in Mkpat Enin Local Government Area. A quasi-experimental design was adopted for the study. The population consisted of 1,871 Senior Secondary School Two (SS2) students, while a sample of 97 students drawn from two co-educational secondary schools was used. The instrument for data collection was the Chemistry Achievement Test on the Periodic Table (CATPT), which had a reliability coefficient of 0.86 using the Kuder–Richardson Formula (K-20). Mean and standard deviation were used to answer the research questions, while Analysis of Covariance (ANCOVA) was used to test the hypotheses at the 0.05 level of significance. The findings showed that there was a significant difference in the performance of students taught using the computer-based visualization model and those taught using the expository instructional method (F = 17.334, p < .05), in favour of the computer-based visualization model. The results also indicated that there was no significant difference in the performance of male and female students exposed to the two instructional methods (p > .05). The study concluded that the use of computer-based visualization improves students’ understanding and performance in the periodic table and provides an effective alternative to conventional teaching methods in Chemistry. It was recommended that Chemistry teachers should make use of computer-based visualization tools when teaching abstract concepts such as the periodic table in Chemistry.